2017
DOI: 10.1139/cjz-2016-0102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and correlation between chemical profiles of cephalic salivary glands and cuticle surface of workers ofApis mellifera(Hymenoptera, Apidae)

Abstract: The cuticle surface of insects displays functions in communication, such as recognition. It is known that oenocytes are responsible for the origin of the compounds found in the epicuticle. Secretion of exocrine glands might be added to the original composition during the insect’s life. The aims of the present study were (i) to quantify and to qualify the chemical compounds in cephalic salivary glands (CSG) and cuticle surface of workers of Apis mellifera L., 1758; (ii) to compare chemical profiles of both glan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 54 publications
4
8
0
Order By: Relevance
“…However, some epidermal cells that function as tegumental glands are also involved in cuticle hydrocarbon synthesis (Kramer & Wigglesworth, 1950;Abdalla et al, 2003) and such compounds can be fully or partially stored in glands after being released as secretion . The present research showed that hydrocarbons were the major compounds in CSG indicating that the studied gland may be an auxiliary source of cuticle hydrocarbons as observed in A. mellifera (Poiani & Cruz-Landim, 2017;Martin et al, 2018). In ants, the postpharyngeal gland (PPG) contains similar hydrocarbons found on cuticle surface (Bagnères & Morgan, 1991;Kaib et al, 2000).…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…However, some epidermal cells that function as tegumental glands are also involved in cuticle hydrocarbon synthesis (Kramer & Wigglesworth, 1950;Abdalla et al, 2003) and such compounds can be fully or partially stored in glands after being released as secretion . The present research showed that hydrocarbons were the major compounds in CSG indicating that the studied gland may be an auxiliary source of cuticle hydrocarbons as observed in A. mellifera (Poiani & Cruz-Landim, 2017;Martin et al, 2018). In ants, the postpharyngeal gland (PPG) contains similar hydrocarbons found on cuticle surface (Bagnères & Morgan, 1991;Kaib et al, 2000).…”
Section: Discussionsupporting
confidence: 55%
“…Thus, in addition to the class III exocrine glands, all glands of ectodermal origin such as tegumental class I gland and exocrine glands structured as organs (Cruz-Landim, 1994) have the potential to contribute to secretion and formation of surface compounds. In fact, cephalic salivary glands (GSC) and Dufour's have been pointed out as source of these hydrocarbons (Kullenberget al, 1973;Bergman & Bergström, 1997;Poiani & Cruz-Landim, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations